DETEKSI MANAJEMEN LABA MENGGUNAKAN M-SCORE BENEISH MODEL - Debbianita Debbianita; Vinny Stephanie Hidayat; Erwan (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2023)
The quality of financial reports is important in the sustainability of a company, quality reports can increase public trust in the company. But often this is misinterpreted by the management by doing various ways to make financial statements look good in the eyes of investors, this is what is called earnings management. During the Covid-19 pandemic that hit the world, of course, there are various challenges to be able to present quality financial reports, this is what researchers are interested in conducting an analysis of the quality of financial reports, especially the banking industry in Indonesia. There are various ways to detect whether there are earnings management actions in the company, one of which is using the M-Score Beneish Model. From the results of the study, it was found that only 18% of the banking industry management carried out earnings management actions